Basics of Quantifying N Sources and Fates on the University of Florida Campus - Jiexuan Luo; George Hochmuth (EDIS, 2016)
Landscapes, recreational areas, and sports fields are important parts of the University of Florida campus that receive nitrogen (N) fertilization to maintain the health and quality of their plants. However, nitrogen can be lost from the landscape through runoff in storm water or leaching into groundwater, both fates leading to pollution of the receiving water bodies. Human activities can also cause losses of nitrogen. Therefore, educating people about nitrogen cycling in the urban environment is critical for the development of solutions to the environmental problems caused by nitrogen loss. This 5-page fact sheet discusses nitrogen mass budgets, land uses in a major university, and nitrogen sources and fates associated with different land uses on campus. Written by Jiexuan Luo and George Hochmuth, and published by the UF Department of Soil and Water Science, April 2015.